2017
DOI: 10.3343/alm.2017.37.5.381
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intact PTH and Bio-Intact PTH Assays Among Non-Dialysis Dependent Chronic Kidney Disease Patients

Abstract: BackgroundThe third-generation bio-intact parathyroid hormone (PTH) (1–84) assay was designed to overcome problems associated with the detection of C-terminal fragments by the second-generation intact PTH assay. The two assays have been compared primarily among dialysis populations. The present study evaluated the correlations and differences between these two PTH assays among patients with chronic kidney disease (CKD) stages 3 to 5 not yet on dialysis.MethodsBlood samples were collected from 98 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
(50 reference statements)
2
6
0
Order By: Relevance
“…The study also suggested that the PTH (1–84) assay may better reflect mineral disorders, probably with more accurate assessment of bone turnover in CKD, but additional confirmatory studies are needed, including bone biopsy [ 16 ]. Many correlations found in our study confirm the pathophysiological relationship between PTH and eGFR, calcium, and inorganic phosphate concentrations in the serum of patients with CKD that have been demonstrated by other authors [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…The study also suggested that the PTH (1–84) assay may better reflect mineral disorders, probably with more accurate assessment of bone turnover in CKD, but additional confirmatory studies are needed, including bone biopsy [ 16 ]. Many correlations found in our study confirm the pathophysiological relationship between PTH and eGFR, calcium, and inorganic phosphate concentrations in the serum of patients with CKD that have been demonstrated by other authors [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…C-PTH fragments are cleared from the circulation through the kidneys, as (1-84) PTH itself, thus accumulating in the blood of patients suffering from CKD [4]. Previous studies have indicated the different levels of iPTH and (1-84)PTH existed both in pre-dialysis [26] and dialysis patients [25,27,28]. It was reported that in people with normal renal function, (7-84)PTH accounted for 20 % of iPTH and for about 50 % in ▶Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, KDIGO recommends using the trend of PTH to guide treatment [4]. In a study performed by Einbinder et al [21] in 2017, iPTH and biointact PTH kits were compared in patients with nondialysis CKD and as expected, the biointact PTH results were lower. Although PTH measurement with biointact PTH is effective, since it targets the first few amino acids at the N-terminal end, it is not yet widely used, either in our country or globally.…”
Section: Discussionmentioning
confidence: 91%